An introduction to ultra-fast silicon detectors - Ferrero, Marco (Sensors series., 2021)
"The book describes the development of innovative silicon sensors known as ultra-fast silicon detectors for use in the space-time tracking of charge particles. The first comprehensive collection of information on the topic, otherwise currently scattered in existing literature, this book presents a comprehensive introduction to the development of ultra-fast silicon detectors with the latest technology and applications from the field. It will be an ideal reference for graduate and postgraduates studying high energy and particle physics and engineering, in addition to researchers in the area. Key features Authored by a team of subject area specialists, whose research group first invented ultra-fast silicon detectors The first book on the topic to explain the details of the design of silicon sensors for 4-dimensional tracking Presents state-of-the-art results, and prospects for further performance evolutions The Open Access version of this book, available at www.taylorfrancis.com/e/9780367646295 , has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license"--